1990
DOI: 10.1021/bi00463a031
|View full text |Cite
|
Sign up to set email alerts
|

An NMR study of the covalent and noncovalent interactions of CC-1065 and DNA

Abstract: The binding of the antitumor drug CC-1065 has been studied with nuclear magnetic resonance (NMR) spectroscopy. This study involves two parts, the elucidation of the covalent binding site of the drug to DNA and a detailed investigation of the noncovalent interactions of CC-1065 with a DNA fragment through analysis of 2D NOE (NOESY) experiments. A CC-1065-DNA adduct was prepared, and an adenine adduct was released upon heating. NMR (1H and 13C) analysis of the adduct shows that the drug binds to N3 of adenine by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…Prior characterization of complexes of ()-CC-1065 with a DNA duplex (Scahill et al, 1990) and duocarmycin A with both a hairpin DNA triplex and duplex (Lin & Patel, 1992;1995) have provided insight into some of the non-covalent interactions stabilizing the ligand in the DNA minor groove. Herein we report the high resolution solution structure of a DNA duplex alkylated by duocarmycin SA (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Prior characterization of complexes of ()-CC-1065 with a DNA duplex (Scahill et al, 1990) and duocarmycin A with both a hairpin DNA triplex and duplex (Lin & Patel, 1992;1995) have provided insight into some of the non-covalent interactions stabilizing the ligand in the DNA minor groove. Herein we report the high resolution solution structure of a DNA duplex alkylated by duocarmycin SA (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…The biological activity of (+)-CC-1065 stems fromitsability toalkylateN3 ofadenine on duplex DNA in a sequence-selective manner and modify the structure and local conformation of DNA (Hurley & Draves, 1993). Previous studies from this laboratory, in collaboration with scientists from The Upjohn Company, have shown that (+)-CC-1065 lies in the minor groove of duplex DNA covering a 4-5-bp region to the 5' side of modified adenine (Hurley et al, 1984;Reynolds et al, 1985;Scahill et al, 1990). As a consequence of formation of the (+)-CC-l065-(N3)-adenine adduct, (+)-CC-1065 induces bending, winding, and stiffening of the DNA (Lee et al, 1991;Sun & Hurley, 1992).…”
mentioning
confidence: 99%
“…NMR analysis has shown that bound CC-1065 spans [5][6] bp in the minor groove of DNA (26). By analogy, a conjugated CDPI3 group probably occupies a similar length of minor groove, with the region of interaction displaced 1-2 bp away from the site of conjugation.…”
Section: Cdpi3-(m14)odni6amentioning
confidence: 99%
“…Communicated by Robert L. Letsinger, Northwestern University, Evanston, IL, December 26,1995 ABSTRACT A minor groove binder (MGB) derivative (N-3-carbamoyl-1,2-dihydro-3H-pyrrolo [3,2- (9), "peptide nucleic acids" (10), C-5-propynyl-containing ODNs (11), 2'-O-methyl-ODNs (12), and N3'-P5'-phosphoramidate ODNs (13).…”
mentioning
confidence: 99%